18bma61c U2
18bma61c U2
18bma61c U2
Note :
Note :
Theorem: (Heine)
Proof:
𝑟𝑘
∴ A ⊆ ⋃𝑚
𝑘=1 𝐵𝑠 (𝑎𝑘 , ) ------(2)
2
Result:
A contraction mapping of any metric space S is
uniformly continuous on S.
Suppose f: S→S is contraction mapping then ∃ 0<α<1 such
that d [ f(x), f(y) ] ≤ d (x,y)
thus give 𝜀>0, ∃ δ = 𝜀 /α such that
d (x,y) < δ ⇒ d (f(x), f(y)) ≤ α. d (x,y) ⇒< α . 𝜀 /α
⇒ f is uniformly continuous on S.
Theorem:
Fixed point theorem:
A contraction of a complete metric space S, is a unique fixed
point p.
Proof:
Let p0 = x
p1 = f(p0)
p2 = f(f(x)) = f(p1)
.
.
.
.
.
pn+1 = f(pn) n= 0, 1, 2, 3,………. ----(1)
Then {pn} is a sequence.
≤ ∑𝑚−1
𝑘=𝑛 αk
= c ∑𝑚−1
𝑘=𝑛 αk
= c ( αn + αn+1 + αn+2 +…+ αn-1)
= c αn ( 1+ α + α2 +………………….+ αm-n )
= c αn ( 1- αm+n) / 1-α
< c αn / 1-α
→0 as αn →0 (when n→∞)
⟹ {pn} is a Cauchy sequence.
But S is a complete metric space. So that sequence {pn}
converges in S.
Let {pn} → p
Now by continuity of f
f (p) = f ( lim pn)
𝑛→∞
= lim f(pn)
𝑛→∞
= lim pn+1 = p
𝑛→∞
f : R→R be defined by
f(x) = 1/x , x≠0
f(0) = A
f (0+) = +∞
f (0-) = -∞
(i.e) f (0+) and f (0-) do not exist.
∴ f has irremovable discontinuity at 0.
(iv) f : R→R
1
sin 𝑖𝑓 𝑥 ≠ 0
f (x) = { 𝑥
𝐴 𝑖𝑓 𝑥 = 0
f has irremovable discontinuity at 0.
Examples:
Let f : ℝ → ℝ be defined by
f (x) = 3x
then f is increasing on ℝ.
-2 < -1
f (-2) = -6
f (-1) = -3
-6 < -3
Consider,
g : ℝ → ℝ defined by
g(x) = 1/x
g is a decreasing
function on R.
Theorem:
If f is increasing on [a, b], then f (c+) and f (c-) both exist for each
c in (a, b) and we have
f (c-) ≤ f (c) ≤ f (c+)
⇒𝛼 − 𝜀 < 𝑓(𝑥₁) ≤ 𝛼 𝑜𝑛 𝑥 ∈ 𝐴
⇒|𝑓(𝑥 ) − 𝛼 | < 𝜀
𝑓(𝑎) ≤ 𝑓(𝑎+)
If 𝑐 = 𝑏 𝑡ℎ𝑒𝑛 𝑓(𝑏+)does not exist for 𝑓 𝑜𝑛 [𝑎, 𝑏] and
𝑓(𝑏−) ≤ 𝑓(𝑏)
Proof:
Let 𝑓 be strictly increasing on S. then
𝑥 < 𝑦 ⇒ 𝑓(𝑥) < 𝑓(𝑦)
(i.e) different elements have different images
⇒ 𝑓 is 1-1 on S
⇒𝑥₁ > 𝑥₂
⇒𝑦₁ > 𝑦₂
Theorem:
Proof:
By theorem,
DIFFERENTIATION
Definition: Difference of Quotient
Let 𝑓 be defined on an open interval(𝑎, 𝑏). Then for two
distinct points 𝑥 and 𝑐 in (𝑎, 𝑏) we can form the quotient
𝑓 (𝑥) −𝑓(𝑐)
𝑥−𝑐
This is called Difference Quotient
Definition: Derivative of 𝒇 (Differentiability of 𝒇 )
Let 𝑓 be defined on an open interval (𝑎, 𝑏) and let 𝑐 ∈ (𝑎, 𝑏) then
𝑓 is said to be differentiable at 𝑐 whenever the limit
𝑓(𝑥) −𝑓(𝑐)
lim exists
𝑥→𝑐 𝑥−𝑐
Successive of Derivatives
𝑓′ is called the first derivative of 𝑓. The second derivative of 𝑓
is 𝑓′′ at 𝑐 and is defined by
𝑓′(𝑥) −𝑓′(𝑐)
𝑓′′(𝑐 ) = lim
𝑥→𝑐 𝑥−𝑐
Notation:
𝑑𝑦
𝑓′(𝑐 ) = |x=c = 𝐷𝑓(𝑐 ) = 𝑦′(𝑐) all denote the first
𝑑𝑥
derivative of 𝑦 = 𝑓(𝑥) at 𝑐
Theorem:
If 𝑓 is defined on (𝑎, 𝑏) and differentiable at a point c in (𝑎, 𝑏),
then there is a function 𝑓* (depending on 𝑓 and on 𝑐) which is
continuous at c and which satisfies the equation
𝑓 (𝑥 ) − 𝑓 (𝑐 ) = (𝑥 − 𝑐 )𝑓 ∗ (𝑥 ) ……(1)
for all 𝑥 is (𝑎, 𝑏) , with 𝑓 ∗ (𝑐 ) = 𝑓′(𝑐). Conversely, if there is a
function 𝑓 ∗, continuous at 𝑐, which satisfies (1), then 𝑓 is
differentiable at c and 𝑓 ′ (𝑐) = 𝑓 ∗ (𝑐 )
Proof:
Let 𝑓 be differentiable at c . Define 𝑓 ∗ on (𝑎, 𝑏) by
𝑓(𝑥) −𝑓(𝑐)
𝑖𝑓 𝑥 ≠ 𝑐
𝑓 ∗ (𝑥 ) = { 𝑥−𝑐
𝑓′(𝑐 ) 𝑖𝑓 𝑥 = 𝑐
This satisfies the equation
𝑓(𝑥 ) − 𝑓(𝑐 ) = (𝑥 − 𝑐 )𝑓 ∗ (𝑥 ) and
𝑓 ∗ (𝑥 ) = 𝑓′(𝑐 )
Now to prove 𝑓 ∗ is continuous at c
(i.e) To prove: As 𝑥 → 𝑐 , 𝑓 ∗ (𝑥 ) = 𝑓′(𝑐 )
𝑓 (𝑥) −𝑓(𝑐)
As 𝑥 → 𝑐 , 𝑓 ∗ (𝑥 ) = lim = 𝑓′(𝑐)
𝑥→𝑐 𝑥−𝑐
= 𝑓 ∗ (𝑐)
Thus 𝑓 ∗ (𝑥 ) → 𝑓 ∗ (𝑐)
⇒𝑓 ∗ is continuous at c.
Conversely,
Let there exist a function 𝑓 ∗ on (𝑎, 𝑏) continuous at c and
which satisfies
𝑓 (𝑥 ) − 𝑓 (𝑐 ) = (𝑥 − 𝑐 )𝑓 ∗ (𝑥 ) ……………..(1)
= 𝑓 ∗ (𝑐) … … … … … (2)
As 𝑓 ∗ is continuous at c, 𝑓 ′ (𝑐) exist. LHS of (2) exist. (i.e) 𝑓 is
differentiable at c. And
𝑓(𝑥) −𝑓(𝑐)
𝑓′(𝑐) = lim
𝑥→𝑐 𝑥−𝑐
⇒ 𝑓 ′(𝑐 ) = 𝑓 ∗ (𝑐 ) 𝑏𝑦( 2)
Hence proved
Theorem:
If 𝑓 is differentiable at c then 𝑓 is continuous at c.
Proof:
Let 𝑓 be differentiable at c. Then the by previous theorem,
Algebra of Derivatives
Theorem:
Assume 𝑓 𝑎𝑛𝑑 𝑔 are defined on (𝑎, 𝑏) and differentiable at c.
Then 𝑓 + 𝑔, 𝑓 − 𝑔 𝑎𝑛𝑑 𝑓. 𝑔 are also differentiable at c. This is also
true of 𝑓 ⁄ 𝑔 if 𝑔(𝑐 ) ≠ 0. the derivatives at c are given by the
following formula.
(i) (𝑓 ± 𝑔)′(𝑐 ) = 𝑓′(𝑐) ± 𝑔′(𝑐)
(ii) (𝑓. 𝑔)′ (𝑐 ) = 𝑓(𝑐 )𝑔′(𝑐 ) + 𝑔 (𝑐 )𝑓 ′ (𝑐 )
𝑓 𝑔(𝑐 )𝑓′ (𝑐 )−𝑓(𝑐)𝑔′(𝑐)
(iii) ( ⁄𝑔 ) ′(𝑐 ) = provided 𝑔(𝑐) ≠ 0
𝑔 (𝑐 )2
Proof:
(𝑓+𝑔)(𝑥) −(𝑓+𝑔)(𝑐)
(i) (𝑓 + 𝑔)′(𝑐 ) = lim
𝑥→𝑐 𝑥 −𝑐
(𝑓 (𝑥) +𝑔(𝑥) )−(𝑓 (𝑐 )+𝑔(𝑐) )
= lim
𝑥→𝑐 𝑥−𝑐
= 𝑓′(𝑐 ) + 𝑔′(𝑐)
Thus if 𝑓 𝑎𝑛𝑑 𝑔 are differentiable at c, then (𝑓 + 𝑔) is differentiable
at c and
(𝑓 + 𝑔)′(𝑐 ) = 𝑓′(𝑐 ) + 𝑔′(𝑐)
Similarly, (𝑓 − 𝑔) is differentiable at c and
(𝑓 − 𝑔)′(𝑐 ) = 𝑓′(𝑐 ) − 𝑔′(𝑐)
Since the R.H.S of (7) exists, the limit on L.H.S also exists
∴ 𝑓𝑔 is differentiable and
(𝑓𝑔)′(𝑐 ) = 𝑓(𝑐 )𝑔′(𝑐 ) + 𝑔 (𝑐 )𝑓′(𝑐)
𝑓 (𝑥) 𝑓 (𝑐 ) 𝑔(𝑐 )𝑓 (𝑥) −𝑓 (𝑐 )𝑔(𝑥)
(iii) − =
𝑔 (𝑥 ) 𝑔 (𝑐 ) 𝑔 (𝑥) 𝑔(𝑐)
𝑓 𝑓
( ⁄𝑔)𝑥−( ⁄𝑔)𝑐 𝑔(𝑐 )𝑓 ∗ (𝑥)−𝑓(𝑐)𝑔 ∗ (𝑥)
lim = lim 2
𝑥→𝑐 𝑥−𝑐 𝑥→𝑐 (𝑔(𝑐 )) +(𝑥−𝑐 )𝑔(𝑐 )𝑔∗ (𝑥)
𝑓 𝑓
( ⁄𝑔)𝑥−( ⁄𝑔)𝑐 𝑔(𝑐 )𝑓 ∗ (𝑥)−𝑓(𝑐 )𝑔 ∗ (𝑥)
lim = lim 2
𝑥→𝑐 𝑥−𝑐 𝑥→𝑐 (𝑔(𝑐 )) +(𝑥−𝑐 )𝑔(𝑐 )𝑔∗ (𝑥)
𝑓 𝑔 (𝑐 )𝑓′(𝑐 )−𝑓(𝑐)𝑔′(𝑐)
⇒( ⁄𝑔) ′(𝑐 ) =
𝑔 (𝑐 )2
R.H.S of (8) exist
𝑓 𝑔 (𝑐 )𝑓′(𝑐 )−𝑓(𝑐)𝑔′(𝑐)
( ⁄𝑔) ′(𝑐 ) = if 𝑔(𝑐) ≠ 0
𝑔 (𝑐 )2
Results:
(i) Derivative of a constant function is zero.
Let 𝑓 ∶ (𝑎, 𝑏) → ℝ. Defined by 𝑓(𝑥 ) = 𝑚 (𝑎 𝑐𝑜𝑛𝑠𝑡𝑎𝑛𝑡)
𝑓 (𝑥) −𝑓(𝑐) 𝑚−𝑚
lim = lim =0
𝑥→𝑐 𝑥−𝑐 𝑥→𝑐 𝑥−𝑐
𝑓′(𝑥 ) = 0
⇒ 𝑓′(𝑥 ) = 1
= 𝑥. 𝑥
= 𝑓₁(𝑥) + 𝑓₂(𝑥)
𝑓′(𝑥 ) = (𝑓₁𝑓₂)′𝑥
= 𝑓₁(𝑥)𝑓₂′(𝑥) + 𝑓₁′(𝑥)𝑓₂(𝑥)
= 𝑥. 1 + 𝑥. 1
𝑓′(𝑥) = 2𝑥
Thus 𝑓 (𝑥 ) = 𝑥 2 ⇒ 𝑓′(𝑥 ) = 2𝑥
= 𝑥 2. 𝑥
= 𝑓₁(𝑥) + 𝑓₂(𝑥)
𝑓′(𝑥 ) = (𝑓₁𝑓₂)′𝑥
= 𝑓₁(𝑥)𝑓₂′(𝑥) + 𝑓₁′(𝑥)𝑓₂(𝑥)
= 𝑥 2 . 1 + 2𝑥. 𝑥 = 3𝑥 2
Proof:
Since 𝑓 is differentiable at c, there exists a function 𝑓
continuous at c ………………(1)
satisfying 𝑓(𝑥 ) − 𝑓 (𝑐 ) = (𝑥 − 𝑐 )(𝑥 ) ∀ 𝑥 ∈ 𝑆 … … … … . (2)
And 𝑓 ∗ (𝑐 ) = 𝑓′(𝑥) ……………………….....(3)
Since g is differentiable at 𝑓(𝑐), there exists a function g*
continuous at 𝑓(𝑐 ).
= 𝑓 ∗ (𝑐 )𝑔∗ (𝑓 (𝑐 ))
𝑓′(𝑐 )𝑔(𝑓′(𝑐 ))
𝑓(𝑥 ) − 𝑓(𝑐)
lim
𝑥→𝑐+ 𝑥−𝑐
exists as a finite value (or) if the limit is +∞ (𝑜𝑟) − ∞. This limit will
be denoted by 𝑓₊′(𝑐)
𝑓 (𝑥) −𝑓(𝑐)
𝑓₊′(𝑐 ) = lim
𝑥→𝑐+ 𝑥−𝑐
𝑓 is said to have the left hand derivative and c is the left hand
limit if
𝑓(𝑥) −𝑓(𝑐)
lim
𝑥→𝑐₋ 𝑥−𝑐
exists as a finite value (or) if the limit is +∞ (𝑜𝑟) − ∞. This limit will
be denoted by 𝑓₋′(𝑐)
𝑓 (𝑥) −𝑓(𝑐)
𝑓₋′(𝑐) = lim
𝑥→𝑐₋ 𝑥−𝑐
Infinite derivatives:
Note:
Theorem:
𝑓 (𝑥 ) < 𝑓 (𝑐 ) 𝑖𝑓 𝑥 < 𝑐
Proof:
𝑓 ∗ continuous at c
satisfying 𝑓 (𝑥 ) − 𝑓 (𝑐 ) = (𝑥 − 𝑐 )𝑓 ∗ (𝑥 ) ∀ 𝑥 𝑖𝑛 𝑆 → 1
𝑓 ∗ (𝑐 ) = 𝑓′(𝑐 ) > 0
⇒𝑓 (𝑥 ) − 𝑓(𝑐 ) and 𝑥 − 𝑐
(𝑥 − 𝑐 ) < 0 ⇒ 𝑓 (𝑥 ) − 𝑓 (𝑐 ) < 0
Suppose, 𝑓′(𝑐 ) = +∞
𝑓 (𝑥) −𝑓(𝑐)
Then lim →∞
𝑥→𝑐 𝑥−𝑐
Theorem:
Proof:
𝑓 ∗ is continuous at c
satisfying 𝑓(𝑥 ) − 𝑓 (𝑐 ) = (𝑥 − 𝑐 )𝑓 ∗ (𝑥 ) ∀ 𝑥 𝑖𝑛 𝑆
𝑥 − 𝑐 < 0 ⇒ 𝑓 (𝑥 ) − 𝑓 (𝑐 ) > 0
𝑥 < 𝑐 ⇒ 𝑓 (𝑥 ) > 𝑓 (𝑐 )
𝑓 (𝑥 ) ≤ 𝑓 (𝑎 ) ∀ 𝑥 𝑖𝑛 𝐵(𝑎) ∩ 𝑆
Note:
Example:
Theorem:
Proof:
∴ 𝑓′(𝑐 ) = 0
Note:
𝑓 (𝑥 ) = 𝑥 3
𝑓′(𝑥 ) = 3𝑥 2
𝑓′(0) = 0
(iii) The fact that c is an interior point of (𝑎, 𝑏)𝑖𝑛 the statement of
above theorem is important.